Speech by Y.A.B. Ketua Menteri Pulau Pinang on the occasion of the Official Opening of Kompleks Tun Abdul Razak phase 1a on January 1, 1977. - Lim, Chong Eu (1977)
On behalf of the State Government of Penang and the Board of the Penang Development Corporation, I take this opportunity to welcome everyone present here this morning to witness the official opening of Phase 1A, Kompleks Tun Abdul Razak.